The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/polym13162775
|View full text |Cite
|
Sign up to set email alerts
|

Properties of High-Density Fiberboard Bonded with Urea–Formaldehyde Resin and Ammonium Lignosulfonate as a Bio-Based Additive

Abstract: The potential of ammonium lignosulfonate (ALS) as an eco-friendly additive to urea–formaldehyde (UF) resin for manufacturing high-density fiberboard (HDF) panels with acceptable properties and low free formaldehyde emission was investigated in this work. The HDF panels were manufactured in the laboratory with very low UF resin content (4%) and ALS addition levels varying from 4% to 8% based on the mass of the dry wood fibers. The press factor applied was 15 s·mm−1. The physical properties (water absorption and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 116 publications
1
22
0
Order By: Relevance
“…They can be OSB, fibreboards or other modern boards [ 39 ]. This is in line with the current trend of the use of eco-friendly wood-based panels in construction [ 40 , 41 ].…”
Section: Introductionsupporting
confidence: 85%
“…They can be OSB, fibreboards or other modern boards [ 39 ]. This is in line with the current trend of the use of eco-friendly wood-based panels in construction [ 40 , 41 ].…”
Section: Introductionsupporting
confidence: 85%
“…They reported that bio-based adhesives of lignin, starch, and tannins can potentially be used to produce eco-friendly wood composite materials. Furthermore, some researchers have extensively studied the potential utilization of lignosulfonates to produce eco-friendly particleboard [ 32 , 33 , 34 ]. Several research groups have used tapioca starch as a bio-binder in bio-insulation materials, including ramie fiber [ 35 ], sugarcane bagasse [ 36 ], water hyacinth [ 37 ], bamboo [ 25 , 38 ], and oil palm empty fruit bunches (OPEFB) [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of lignosulfonates to the performance of the engineered wood panels is presented in several papers. Calcium lignosulfonate [38] magnesium and sodium lignosulfonates [39], ammonium lignosulfonate [40][41][42] or modified ammonium lignosulfonate [43] were used as adhesives for lowering formaldehyde emission and improve the mechanical properties of the panels. A mixture of phenol formaldehyde adhesives and lignosulfonate (up to 20% of lignosulfonate in the adhesives) was shown to improve the shear strength of wood glued joints gradually [44].…”
Section: Introductionmentioning
confidence: 99%